Role of Impurities in Silicon Solidification and Electrical Properties Studied by Complementary In Situ and Ex Situ Methods. Issue 17 (2nd August 2019) - Ouaddah, Hadjer; Périchaud, Isabelle; Barakel, Damien; Palais, Olivier; Di Sabatino, Marisa; Reinhart, Guillaume; Regula, Gabrielle; Mangelinck-Noël, Nathalie
Abstract : All silicon (Si) ingot fabrication processes share challenges to control grain structure, defect, and impurity contamination during the solidification step to improve the material properties. The final grain structure and inherent structural defects issued from the solidification step are responsible for the photovoltaic (PV) properties for a large part, all the more as they are often associated with impurity distribution. Impurities play a major role as they not only can modify the development of the grain structure formation but can also interact with structural defects creating the regions of deleterious minority carrier lifetime recombination. Samples containing different levels of impurities and solidified with different processes are selected and analyzed as‐grown or observed by X‐ray imaging during resolidification from as‐grown seeds. The growth features and relative crystallographic orientation of neighbor grains are characterized. Moreover, minority carrier lifetime measurements are performed and correlated with the growth features. The complementarity of the different techniques improves the understanding of phenomena at stake during the formation of grains and twins, the effect of impurities, and their impact on photovoltaic properties. The results show the significant influence of light and metallic impurities, such as copper, on the grain structure and on the electrical properties. Abstract : Grain structures and electrical properties are studied in silicon contaminated with impurities. The presence of carbon induces a higher amount of grain nucleation, resulting in the high‐order twin and random angle grain boundaries. Cu can lead to solid–liquid interface destabilization. Lifetime maps demonstrate the influence of impurities on the electrical activity in relation to the crystallographic defects and grains.